ANALISIS NILAI SOSIAL PADA NOVEL BILA MALAM BERTAMBAH MALAM KARYA PUTU WIJAYA DENGAN PENDEKATAN MIMETIK (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
Every literary work must have the social values ​​of life contained in it, whether conveyed implicitly or explicitly. Like the novel Bila Malam Bertambah Malam by Putu Wijaya, it contains many social values ​​and so on. With these problems, this research article is written to discuss "Analysis of Social Values ​​in the novel Bila Malam Bertambah Malam by Putu Wijaya using the mimetic approach”. This research was conducted using qualitative descriptive research methods. Data collection techniques carried out, in the form of documentation, as well as research instruments were the researchers themselves using a check list of the classification of research materials and notes of observations. The data analysis technique in this study is a descriptive interpretive technique, where the researcher tries to describe the opinions and views that are on an object of research. This article aims to find out the social values ​​contained in the novel Bila Malam Bertambah Malam by Putu Wijaya. The results of this study indicate that social problems cannot be separated from the relationships that accompany them. These relationships include human problems with humans, human problems with oneself and human problems with culture.